2022
DOI: 10.1039/d2se00663d
|View full text |Cite
|
Sign up to set email alerts
|

The role of A-site composition in the photostability of tin–lead perovskite solar cells

Abstract: The efficiency of tin-lead perovskite solar cells (TLPSC) has been consistently increasing. However, their photostability continues to be a persistent challenge. Besides the oxidation of tin (Sn), the presence of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 57 publications
(103 reference statements)
2
12
0
Order By: Relevance
“…Mixed cations in the A site first became popular in lead-based perovskites, resulting in higher stability and PCEs. [107][108][109] As expected, mixed A-site Sn-based perovskites have also been successful. Mixed cations MA and Cs were introduced by Liu et al [110] however, the PSCs suffered low PCEs which was mainly attributed to a poor open-circuit voltage of 0.22 V. Zhao et al [111] later introduced mixed MA and FA cations, and showed that the optical properties of Sn-based perovskites were influenced by the ratios of the mixed cations.…”
Section: Mixed A-site Sn-halide Perovskitessupporting
confidence: 68%
See 1 more Smart Citation
“…Mixed cations in the A site first became popular in lead-based perovskites, resulting in higher stability and PCEs. [107][108][109] As expected, mixed A-site Sn-based perovskites have also been successful. Mixed cations MA and Cs were introduced by Liu et al [110] however, the PSCs suffered low PCEs which was mainly attributed to a poor open-circuit voltage of 0.22 V. Zhao et al [111] later introduced mixed MA and FA cations, and showed that the optical properties of Sn-based perovskites were influenced by the ratios of the mixed cations.…”
Section: Mixed A-site Sn-halide Perovskitessupporting
confidence: 68%
“…Mixed cations in the A site first became popular in lead‐based perovskites, resulting in higher stability and PCEs. [ 107–109 ] As expected, mixed A‐site Sn‐based perovskites have also been successful. Mixed cations MA and Cs were introduced by Liu et al.…”
Section: Composition Engineeringsupporting
confidence: 53%
“…Accounting for A-site engineering alone, the Sn-Pb-HPSCs also demonstrated improvement in PCE with slightly better device stability. [72,242] X-site engineering by incorporating a small amount of Br and Cl into Sn-Pb-HPSCs reduces nonradiative recombination at grain boundaries of Sn-Pb perovskite, leading to better device performances. [243,244] Additionally, Wang et al used alkylammonium pseudohalide as a functional pseudohalide additive in MA-free Sn-Pb-HPSCs, improving the film formation and inhibited iodine vacancies.…”
Section: B-site Modulated: Pb/sn/ge-based Hpscsmentioning
confidence: 99%
“…Similar to the development of Pb-based PSCs, the selection of the A-site cation in TLSPCs gradually evolved from single- to mixed-cation compositions (Figure ). Driven by the high and reproducible efficiencies above 20%, the combination of MA and FA (or MAFA) has been established as one of the most reported compositions. ,, Nevertheless, diverse thermal stability and photostability experiments on this composition have revealed at least ∼20% PCE losses after 250 h under stress. ,, As mentioned in Reaction , the loss of MA after thermal treatment (even as low as 50 °C) is typically acknowledged as the main reason behind the limited stability of MAFA compositions. , Further insights into the device photostability have consistently shown that the compositions with contents of MA ≥ 20% lead to a rapid efficiency drop during the initial minutes of operation. ,, The reason behind this drop has been attributed to several factors related to ion migration and/or to the appearance of nanosized Sn y /Pb (1‑ y ) I 2 aggregates on the film surface, which can further act as recombination centers and accelerate the perovskite degradation . While the nature of these aggregates is not clear, it is plausible that they are unreacted precursors caused by fast crystallization.…”
Section: Influence Of Perovskite Composition On Operational Stabilitymentioning
confidence: 99%
“…34,35 Further insights into the device photostability have consistently shown that the compositions with contents of MA ≥ 20% lead to a rapid efficiency drop during the initial minutes of operation. 31,32,36 The reason behind this drop has been attributed to several factors related to ion migration 36 and/or to the appearance of nanosized Sn y /Pb (1-y) I 2 aggregates on the film surface, which can further act as recombination centers and accelerate the perovskite degradation. 32 While the nature of these aggregates is not clear, it is plausible that they are unreacted precursors caused by fast crystallization.…”
Section: ■ Influence Of Perovskite Composition On Operational Stabilitymentioning
confidence: 99%